Severity prognostic factors in patients with acute pancreatitis in Hospital Nacional Sergio E. Bernales: Factores pronósticos de severidad en pacientes con pancreatitis aguda en el servicio de gastroenterología del Hospital Nacional Sergio E. Bernales durante el periodo junio 2016-junio 2018 - Jamanca-Milian, Hellen (2019)
Objective: To determine the prognostic factors of severity in patients with acute pancreatitis (AP) at the Hospital Nacional Sergio E. Bernales during the period June 2016 to June 2018. Methods: Study of cases and controls, being the cases patients with AP moderately severe or severe and controls those of mild AP. The medical records were reviewed to apply the APACHE-II score. Chi- square was used and the ORs were obtained with their respective 95% CI. SPSS 25 program was used. Results: 162 medical records were reviewed. 54 (33.3%) patients developed AP moderately severe or severe and 108 (66.7%) had mild AP. Of the patients with AP moderately severe or severe, 55.6% were men; while in mild AP the female sex was predominant with 91.7%. The majority were of biliary origin (83.3%). There was a predominance of mild AP. AP moderately severe or severe was associated with being over 60 years old (OR: 3.10; 95% CI: 1.26-7.65; p= 0.011), presenting pleural effusion (OR: 7.78 95% CI: 5.745-54.418 ; p <0.001), hematocrit>40% (OR: 4.17; 95% CI: 2.07-8.39; p <0.001) and APACHE score ≥8 (OR: 7.88; 95% CI: 3.77-16.45; p<0.001). Conclusions: The factors associated with the severity of pancreatitis were age, presenting pleural effusion, hematocrit> 40% and APACHE score ≥8.